Does age matters: unveiling the impact of age on decompressive craniectomy outcomes in malignant middle cerebral artery infarction: insights from an Indian single-center study - Prem Kumar Reddy Gopireddy; Rahul Sharma; Anand Katkar; Ashok Bhanage; Chintan Popat (Egyptian Journal of Neurosurgery)
Abstract Background Malignant middle cerebral artery infarction is a life-threatening form of ischemic stroke characterized by severe cerebral edema and rapid neurological deterioration. Decompressive craniotomy is a surgical intervention aimed at reducing intracranial pressure and preventing brain herniation. This study evaluates the outcomes of Decompressive Craniectomy in malignant Middle Cerebral Artery infarction focusing on age and comorbidities. Results In this cohort of 32 patients with malignant Middle Cerebral Artery infarction, early surgical intervention (< 48 h) significantly improved outcomes (p ≈ 0.02), with 17 (65.4%) achieving modified Rankin Scale 0–2. Age was not a significant predictor of recovery (p ≈ 0.06), as favorable outcomes were seen across all age groups. Comorbidities strongly influenced prognosis; 13 (81.25%) of patients without comorbidities showed significantly better recovery (81.25% improved, p ≈ 0.001). Gender differences were also notable- 15 (62.5%) males had higher improvement rates compared to 3 (37.5%) females, with a significant association (p ≈ 0.02). Conclusion Our study shows that age alone doesn’t determine recovery after decompressive craniectomy for malignant Middle Cerebral Artery infarction. Instead, early surgery and the presence of comorbidities had a greater impact on outcomes. Decisions should focus on a patient’s overall condition, not just age, as older patients can also recover well.